Career success for women academics in higher education: Choices and challenges - Noëlle Obers, Noëlle Obers (South African Journal of Higher Education, 2016)
The aim of the research reported on in this paper is to contribute to an understanding of how women academics experience career success; how their choices and challenges impact on their career advancement and how the playing fields in academia can be levelled. Understanding the constraints and identifying enabling aspects may help women academics overcome obstacles in their career development and be more represented in academia and ultimately in society. This research was a case study undertaken at one institution, Rhodes University. Data were collected from Institutional documents, questionnaire data from women academics at the Institution and in-depth interviews with six women academics. The data indicate that mentoring is a strategy to enhance levels of self-esteem and research productivity and ultimately improve the representation of women in leadership and senior positions.